Displaced Commercial Risk Pada Lkms: Tinjauan Hukum Ekonomi Syariah Dan Respons Terhadap Volatilitas Suku Bunga - Muhamad Afif Sholahudin; Mega Silvia (Gunung Djati Conference Series, 2026)
The phenomenon of Displaced Commercial Risk (DCR) presents a real challenge for Islamic Microfinance Institutions (LKMS) operating in a dual financial system. DCR occurs when LKMS feel compelled to adjust their financing margins following fluctuations in central bank interest rates to maintain competitiveness with conventional financial institutions. This study aims to analyze the forms and manifestations of DCR in LKMS practices, trigger LKMS responses to interest rate volatility, and examine its compliance with Islamic economic principles. Using a qualitative-descriptive approach with case study and juridical-normative methods, data were collected through literature studies and regulatory documentation. The results show that DCR manifests in margin determination that is no longer entirely based on the risk and real value of the business, but instead indirectly follows conventional benchmarks. This has the potential to deviate from the principles of fairness and risk sharing in Islamic economics. This study recommends the development of a real-value-based margin determination model, strengthening Islamic regulations, and increasing customer literacy to strengthen the integrity and sustainability of LKMS.